The effect of grouping and room condition on student's competency evaluation. - Gabuyog, Ricky Catalan; Romulo, Joyce Salvador (1999.)
This study wanted to find out which of the two groups is effective, with group interaction or without group interaction. It also sought to know if the students evaluate themselves highly competent if they are subjected to a well-lighted or to a poorly-lighted room. The respondents were 60 Broadcast Communication students from the Division of Humanities from four different year levels. Subjects were selected using the stratified random sampling. The design was a 2 (with group interaction and without group interaction) x 2 (well lighted and poorly lighted room) factorial design and this tested the three hypotheses (1) To find out whether the students with group interaction would get high scores in compentency evaluation. (2) To know if students subjected to a well lighted room condition score higher than those students in a poorly-lighted room. (3) To determine whether the combined effects of group interaction and a well-lighted room will bring high score on student's competency evaluation., The researchers used the 2 x 2 Analysis of Variance (ANOVA) in the analysis of data. The results showed that (1) students who interacted with others scored higher in their competency evaluation than those who were not allowed to interact; (2) room condition has no significant effect on student's competency evaluation; and (3) there was no interaction between grouping and the room condition.
Research Paper (Undergraduate, Bachelor of Arts in Psychology) College of Arts and Sciences, University of the Philippines in the Visayas, Miagao, Iloilo.
Keywords: Student's Competency Evaluation